Affordances of physical objects as a material mode of representation: A social semiotics perspective of hands-on meaning-making - Tang, Kok-Sing; Jeppsson, F.; Danielsson, K.; Bergh Nestlog, E. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This paper examines the affordances of physical objects (e.g. apparatus, models, manipulatives) as they were used by teachers and students to make meaning in coordination with their speech and gestures. Despite the pervasive use of physical objects as material and tactile resources in hands-on investigations or demonstrations, there have been few attempts to analyze their role and function in meaning-making, in the same way, that researchers have previously done for other modes of representation such as speech, written text, diagram and gesture. Using social semiotics as a theoretical framework, we conceptualise physical objects as a semiotic mode with a particular affordance for making meaning that involves embodied actions and manipulation of tools. Based on a multimodal discourse analysis of numerous classroom situations, we illustrate how physical objects as a mode have four unique affordances for meaning-making in science classrooms. These affordances are: (a) enacting material interaction, (b) providing evidential meaning, (c) orientating three-dimensional spatial meaning and (d) sensitising experiential meaning. The implication of why we should use physical objects to support or value-add science meaning-making is then discussed.